Rhetorical Strategies and Code-Mixing in TGB Zainul Majdi’s NWDI Anniversary Speech - Fakihuddin, Lalu; Al Pansori, Muh Jaelani; Wijaya, Herman; Irfan, Muh.; Setiyoningsih, Titi (Journal of Language and Literature Studies, 2026)
Studies of religious speech have often focused on thematic content and textual meaning, while giving limited attention to the interplay between rhetorical strategies and code-mixing within a pragmatic discourse framework. This gap is especially evident in the speeches of locally rooted yet nationally influential religious figures such as TGB Zainul Majdi in Lombok. This study aims to identify the forms of code-mixing in TGB’s speech at the NWDI Hultah event, analyze the rhetorical strategies employed through ethos, pathos, and logos, and explain the social and communicative functions of these linguistic resources. The study employed a descriptive qualitative design using critical discourse analysis, supported by sociolinguistic and pragmatic perspectives. The data consisted of speech transcripts and contextual video documentation, collected through documentation and non-participatory observation and validated through source and theory triangulation. The analysis involved identifying code-mixing patterns, interpreting rhetorical strategies, and examining their communicative functions in context. The findings show that code-mixing among Arabic, Indonesian, and Sasak is strategic rather than incidental. The dominant forms are intrasentential and emblematic code-mixing, with occasional intersentential switching. Arabic reinforces sacred meaning and religious authority, Sasak strengthens cultural intimacy and local solidarity, and Indonesian serves as the main medium for broader message delivery. These linguistic choices support ethos, intensify pathos, and structure logos, making the discourse more persuasive, culturally resonant, and inclusive for multilingual audiences. This study highlights code-mixing as an important discursive resource in contemporary da'wah and contributes to the study of religious discourse, rhetoric, and multilingual communication.